ENRICHMENT OF PASTA PRODUCTS USING BEETROOT - Péter SIPOS (Stefan cel Mare University of Suceava, 2017)
Beetroot has numerous advantageous health effects due its chemical composition, such as fibres, mineral elements, vitamins and phenolic compounds. It has not only anti-tumour effects but its consumption is favourable for the cardiovascular system, too. It is used as natural colouring agent in several products. In this research wheat pasta products were made with 8 and 16% beetroot juice and pulp addition to evaluate that the advantageous nutritional effects of beetroot could be utilized in pasta production as well and the consumer’s opinion on these products. Besides the general physical parameters (dry matter content, drying water loss, cooking water absorption) total phenol content and flavonoid concentrations were measured and a sensory analysis was performed. It was found that the beetroot addition did not influence the most the physical properties of pasta as compared to the control, but the use of beetroot pulp resulted in a significant increase in the water absorption during cooking. Unfortunately the high polyphenol content of beetroot could not be utilized in pasta consumption. Although the dry pasta had significant total phenol content, the cooking led to serious leaching and the same value were experienced as for the control pasta. Despite these facts, this kind of product can be beneficial for the producers as the sensory analysis showed that the overall acceptance and the taste and texture were found to be advantageous for potential consumers.